Caries experience in a severely obese adolescent population - ISABELLE BAILLEUL-FORESTIER, KARINE LOPES, MOURAD SOUAMES, SYLVIE AZOGUY-LEVY,MARIE-LAURE FRELUT, & (IAPD and Blackwell, 2007)
The prevalence of obesity in children has increased worldwide, especially among those with a low socio-economic background.